Hunting in the seas: population status and community perspectives on giant clams (Tridacnidae) and Napoleon wrasse (Cheilinus undulatus), endangered marine taxa of the Wallacea Region, Indonesia. Issue 1 (March 2020) - Yusuf, S; Moore, A M
Abstract: Giant clams (Tridacnidae) and the Napoleon wrasse (Cheilinus undulatus) are valued fisheries commodities for local consumption and trade. Heavy exploitation has greatly reduced their abundance in the Wallacea Region. This study on giant calm and Napoleon wrasse around Sulawesi is based on data from biophysical (SCUBA diving) and socioeconomic surveys from 2004 to 2016 in the Spermonde Archipelago and around Selayar Island, South Sulawesi; and in Central Sulawesi (primarily in the Togean Islands) between 2001 and 2015. Giant clam population abundance declined, with some larger species ( Tridacna gigas, T. derasa, T. squamosa, Hippopus porcellanu s) no longer found at many sites. Despite increasing awareness regarding the protected status of giant clams, exploitation has continued, including mass collection for traditional festivals in the South Sulawesi islands. Specifically intended for export, fishing uses destructive methods, Napoleon wrasse abundance also declined. Habitat (coral reef) degradation likely also had a negative impact. Low densities could threaten reproductive success. Effective protection measures are needed to rebuild depleted giant calm and Napoleon wrasse populations. This is done to promote the natural process of reproduction and recruitment, and degraded habitat should be rehabilitated through passive or active coral reef restoration. Ex-situ (hatchery) breeding and restocking could speed the recovery of depleted giant clam populations.